Comparative efficacy and toxicity of two vaccine candidates against Sporothrix schenckii using either Montanide™ Pet Gel A or aluminum hydroxide adjuvants in mice - Portuondo, Deivys Leandro [UNESP]; Batista-Duharte, Alexander [UNESP]; Ferreira, Lucas Souza [UNESP]; de Andrade, Cleverton Roberto [UNESP]; Quinello, Camila [UNESP]; Téllez-Martínez, Damiana [UNESP]; de Aguiar Loesch, Maria Luiza [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Elsevier, 2017)
Sporotrichosis is an important zoonosis in Brazil and the most frequent subcutaneous mycosis in Latin America, caused by different Sporothrix species. Currently, there is no effective vaccine available to prevent this disease. In this study, the efficacy and toxicity of the adjuvant Montanide™ Pet Gel A (PGA) formulated with S. schenckii cell wall proteins (ssCWP) was evaluated and compared with that of aluminum hydroxide (AH). Balb/c mice received two subcutaneous doses (1st and 14th days) of either the unadjuvanted or adjuvanted vaccine candidates. On the 21st day, anti-ssCWP antibody levels (ELISA), the phagocytic index, as well as the ex vivo release of IFN-γ, IL-4, and IL-17 by splenocytes and IL-12 by peritoneal macrophages were assessed. Cytotoxicity of the vaccine formulations was evaluated in vitro and by histopathological analysis of the inoculation site. Both adjuvanted vaccine formulations increased anti-ssCWP IgG, IgG1, IgG2a, and IgG3 levels, although IgG2a levels were higher in response to PGA+CWP100, probably contributing to the increase in S. schenckii yeast phagocytosis by macrophages in the opsonophagocytosis assay when using serum from PGA+CWP100-immunized mice. Immunization with AH+CWP100 led to a mixed Th1/Th2/Th17 ex vivo cytokine release profile, while PGA+CWP100 stimulated a preferential Th1/Th2 profile. Moreover, PGA+CWP100 was less cytotoxic in vitro, caused less local toxicity and led to a similar reduction in fungal load in the liver and spleen of S. schenckii- or S. brasiliensis-challenged mice as compared with AH+CWP100. These results suggest that PGA may be an effective and safe adjuvant for a future sporotrichosis vaccine.
Keywords: Adjuvant; Aluminum hydroxide; Cytotoxicity; Immunogenicity; Montanide™ Pet Gel A; Sporothrix brasiliensis; Sporothrix schenckii; Vaccine